Highly Selective MIF Ketonase Inhibitor KRP-6 Diminishes M1 Macrophage Polarization and Metabolic Reprogramming - Eszter Vámos; Nikoletta Kálmán; Eva Maria Sturm; Barsha Baisakhi Nayak; Julia Teppan; Viola Bagóné Vántus; Dominika Kovács; Lilla Makszin; Tamás Loránd; Ferenc Gallyas; Balázs Radnai (MDPI AG, 2023)
Macrophage polarization is highly involved in autoimmunity. M1 polarized macrophages drive inflammation and undergo metabolic reprogramming, involving downregulation of mitochondrial energy production and acceleration of glycolysis. Macrophage migration inhibitory factor (MIF), an enigmatic tautomerase (ketonase and enolase), was discovered to regulate M1 polarization. Here, we reveal that KRP-6, a potent and highly selective MIF ketonase inhibitor, reduces MIF-induced human blood eosinophil and neutrophil migration similarly to ISO-1, the most investigated tautomerase inhibitor. We equally discovered that KRP-6 prevents M1 macrophage polarization and reduces ROS production in IFN-γ-treated cells. During metabolic reprogramming, KRP-6 improved mitochondrial bioenergetics by ameliorating basal respiration, ATP production, coupling efficiency and maximal respiration in LPS+IFN-γ-treated cells. KRP-6 also reduced glycolytic flux in M1 macrophages. Moreover, the selective MIF ketonase inhibitor attenuated LPS+IFN-γ-induced downregulation of PARP-1 and PARP-2 mRNA expression. We conclude that KRP-6 represents a promising novel therapeutic compound for autoimmune diseases, which strongly involves M1 macrophage polarization.